SOCIAL MEDIA'S EFFECT ON MUSLIM PERSPECTIVES AND FAMILY'S PREVENTIVE MEASURES FOR INTERFAITH RELATIONSHIPS - Raihana, Siti Nazla; Ghufron, Salma Nuha (IAIN Kendari, 2024)
This research investigates the influence of social media on the Muslim community's perception of interfaith relationships. Focus is also given to the preventive measures taken by families in the face of this phenomenon. The research method involved social media content analysis and interviews with various relevant parties. The findings show that social media has a significant role in shaping public views and lives, especially among the younger generation. In the context of interfaith relationships, social media, particularly through the role of influencers, can change public perception and acceptance of this phenomenon. In the context of preventing children's involvement in interfaith relations, families play an important role. Preventive strategies involve early religious education to shape religious values, social media monitoring, providing positive motivation, creating a harmonious family environment, and providing an understanding of the consequences and challenges that may be faced. The preventive measures taken by families reflect efforts to maintain religious and cultural values. The conclusions of this study underscore the importance of open dialogue, education, and regulations that tighten laws on interfaith relations. The implications of this study can help develop a wise and balanced approach to this phenomenon in Indonesian Muslim society.